Data for article "Terrestrial organic matter input causes dual effects on methylmercury accumulation in coastal planktonic food webs" - Björn, Erik (Umeå University, 2026)
Metadata for mesocosm experiment for the scientific article: "Terrestrial organic matter input causes dual effects on methylmercury accumulation in coastal planktonic food webs"

Metadata för mesokosmexperiment tillhörande vetenskaplig artikel "Terrestrial organic matter input causes dual effects on methylmercury accumulation in coastal planktonic food webs"
Data för artikel "Terrestrial organic matter input causes dual effects on methylmercury accumulation in coastal planktonic food webs"
Keywords: food webs; näringsvävar; methylmercury; metylkvicksilver; bioaccumulation; bioackumulering; thiol compounds; tiolföreningar; dissolved organic matter; löst organiskt material; food web structure; näringsvävstruktur; Natural Sciences; Naturvetenskap; Environmental Sciences; Miljövetenskap